Influence Of Two Novel Compatibilizers On The Properties Of LDPE/Organoclay Nanocomposites - Beg, M. D. H.; Zaman, Haydar U. (Walter de Gruyter GmbH, 2014)
In the present investigation, low density polyethylene (LDPE)/organoclay nanocomposites with various clay contents (1–7 wt%) were prepared via a melt mixing technique, using two different compatibilizers with various contents; low molecular weight trimethoxysilyl-modified polybutadiene (Organosilane) and low molecular weight oxidized polyethylene (OxPE). The effects of incorporation of compatibilizers and clay contents on the mechanical and thermal properties of the nanocomposites were investigated. The dispersibility of silicate clay in the nanocomposites was investigated by transmission electron microscopy (TEM). It was found that organosilane yielded better clay dispersion and a more exfoliated structure compared with the OxPE. Rheological behavior of the samples was examined by a dynamic oscillatory rheometer in the linear viscoelastic region. The organosilane compatibilized system conferred higher tensile strength, yield strength and tensile modulus than those of an uncompatibilized system, and even higher than those of the OxPE compatibilized case. The crystallization behaviors of uncompatibilized and compatibilized nanocomposites were investigated using differential scanning calorimetry (DSC). DSC results indicated that the addition of compatibilizers increased the crystallization temperature (Tc) as a result of heterogeneous nucleation effect of clay on LDPE.